1997
DOI: 10.1139/f97-091
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology and cytogenetic evaluation of Pacific herring larvae exposed to petroleum hydrocarbons in the laboratory or in Prince William Sound, Alaska, after the Exxon Valdez oil spill

Abstract: Following the 1989 Exxon Valdez oil spill in Prince William Sound, Alaska, USA, Pacific herring (Clupea pallasi) larvae sampled from oiled sites had ascites, pericardial edema, and genotoxic damage. Laboratory study confirmed that these lesions were consistent with oil exposure. Pacific herring larvae were trawled from two oiled and two unoiled sites in Prince William Sound in May 1989. Larvae from oiled sites were shorter, had ingested less food, had slower growth (oiled, 0.07-0.10 mm/day; unoiled, 0.15-0.18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
48
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 24 publications
(51 reference statements)
8
48
0
1
Order By: Relevance
“…Pacific herring were a focal species for natural resource injury assessments following the Exxon Valdez (41) (Alaskan waters) and Cosco Busan oil spills (38) (California Current). Herring early life stages exposed to both oil types, in both the field and the laboratory, developed cardiotoxic defects in the form of bradycardia (38) and pericardial edema (38,41), with strikingly similar results to those reported here for subtropical spawning pelagic fish. The remarkably consistent morphological and physiological responses to oil across diverse fish species indicate that the core mechanisms of PAH-induced cardiotoxicity are conserved.…”
Section: Discussionsupporting
confidence: 81%
“…Pacific herring were a focal species for natural resource injury assessments following the Exxon Valdez (41) (Alaskan waters) and Cosco Busan oil spills (38) (California Current). Herring early life stages exposed to both oil types, in both the field and the laboratory, developed cardiotoxic defects in the form of bradycardia (38) and pericardial edema (38,41), with strikingly similar results to those reported here for subtropical spawning pelagic fish. The remarkably consistent morphological and physiological responses to oil across diverse fish species indicate that the core mechanisms of PAH-induced cardiotoxicity are conserved.…”
Section: Discussionsupporting
confidence: 81%
“…These are characterized as #uid "lling the peritoneal cavity, causing pericardial edema or hydropericardium (Marty et al, 1997). Edema has previously been shown to be responsible for larval mortality (Carls et al, 1999).…”
Section: Fig 4 (A)mentioning
confidence: 99%
“…Evidence of population effects is strongest for pink salmon, for which studies of embryos in spawning gravels in the intertidal zone of streams crossing oiled beaches demonstrated elevated mortality for at least 4 y after the spill (2)(3)(4). Laboratory studies subsequently showed that water contaminated with PAHs in the low parts per billion (ppb or μg/L) dissolved from oiled gravel produced a characteristic syndrome of edema in both species (5)(6)(7)(8). Moreover, a series of mark and recapture studies with pink salmon found that morphologically normal juveniles that survived embryonic exposure to water containing <20 μg/L total PAHs had elevated rates of postrelease mortality in the marine environment, with an average reduction in adult survival by 36% (6,9,10).…”
mentioning
confidence: 99%